2014
DOI: 10.1093/intimm/dxu068
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of T-cell IFN-γ and miR-29a expression during active pulmonary tuberculosis

Abstract: IFN-γ is crucial for protection against Mycobacterium tuberculosis. miR-29 was recently shown to non-redundantly inhibit IFN-γ. Here, we investigated IFN-γ and miR-29a expression dynamics of CD4(+) T cells from patients during active tuberculosis (TB) (n = 32) and in household contacts who were latently M. tuberculosis infected (n = 19) from Ghana. Whereas M. tuberculosis-specific IFN-γ expression was similar during TB chemotherapy, superantigen stimulation indicated generally impaired IFN-γ expression in TB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…With regard to M . tuberculosis studies, this miRNA has been identified as a serological biomarker [ 43 ] and was shown to be differentially expressed in leukocytes during TB infection [ 47 , 48 ]. MiR-29a has also been reported to be increased in human macrophages in response to M .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to M . tuberculosis studies, this miRNA has been identified as a serological biomarker [ 43 ] and was shown to be differentially expressed in leukocytes during TB infection [ 47 , 48 ]. MiR-29a has also been reported to be increased in human macrophages in response to M .…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of healthy contacts (n = 19) and tuberculosis patients (n = 32) was tested for M . tuberculosis PPD-specific immune response before and showed significant IFNγ expression [77]. We took heparinised blood (up to 30 ml) from each donor.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, another group reported decreased expression of miR-26a, miR-29a, and miR-142-3p in whole blood in children with tuberculosis compared to healthy children with latent Mtb infection (LTBI) 139 . However, Awuah et al concluded that although median miR-29a expression was slightly higher in TB patients, there was no significant difference compared with LTBI patients 140 . These plausible results might be due to choices of patients and starting material for miRNA quantification.…”
Section: Mirnas As Biomarkers For Bacterial Infectionmentioning
confidence: 97%